Prescription and cost-analysis of antiemetic medication use in pediatric wards: a prospective observational study - Patel, Maulik M.; Rana, Devang A.; Patel, Varsha J.; Patel, Manish (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Use of anti-emetic drugs in pediatric population is often warranted, but choice of drug remains questionable within pediatricians. Objective of current study is: to study prescribing pattern and to calculate cost of antiemetic drug therapy in pediatric wards. Methods: A prospective, observational study was conducted in pediatric wards of a tertiary care hospital of over 14 month’s duration. Institutional ethics committee approval was obtained and written informed consent of parents/guardians was taken. Data of any pediatric patient receiving anti-emetic agent were included in the study. Results: A total of 218 prescriptions were collected. Mean age of patients was 4.39±3.16 (range 4 months to 12 years). Gastroenteritis was the most frequently diagnosed disease in 137(63%) patients. Domperidone was prescribed in 52.4% and ondansetron in 47.6% children. Oral liquid dosage formulation was prescribed in 109 (48.4%) followed by solid dosage form 47 (20.9%). Mean cost of domperidone therapy was 25.34±6.55 INR and for ondansetron it was 36.62±17.94 INR. Conclusions: Gastroenteritis was most frequent indication for use of anti-emetics. Domperidone pharmacotherapy was cheaper and most frequently prescribed than ondansetron.